FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI - Maria Yustina Melika; Ismansyah Ismansyah; Rivan Firdaus (MNJ (Mahakam Nursing Journal), 2023)
Hypertension is a deadly disease if not prevented because it affects other body organ systems. The design of this study used descriptive correlations with a cross-sectional approach conducted in May 2022. The study population consisted of all hypertensive patients at Mencimai Barong Tongkok West Kutai sub-health center, a total of 43 patients. Total sampling was used to determine the study population, and the study sample consisted of 43 respondents. The hypothesis Ha is accepted if the statistical test by Chi-square yields a t-count (p-value) < 0.05. The results of the statistical test show that there is a relationship between physical activity and body mass index and the incidence of hypertension (pvalue = 0.00). There is no relationship between age (pvalue = 0.75), occupation (pvalue = 0.35), and gender (pvalue = 0.72) and the incidence of hypertension. Body mass index and physical activity are factors associated with the incidence of hypertension in the work zone of Mencimai Barong Tongkok Kutai Barat Sub-Health Center. Keywords: Hypertension, Body Mass Index, Health Center.